2011
DOI: 10.1603/ec10442
|View full text |Cite
|
Sign up to set email alerts
|

Application of Molecular Techniques to Identification of Three Plusiine Species, Autographa nigrisigna, Macdunnoughia confusa, and Thysanoplusia intermixta (Lepidoptera: Noctuidae), Found in Integrated Pest Management Lettuce Fields in Japan

Abstract: Three plusiine species, Autographa nigrisigna, Macdunnoughia confusa, and Thysanoplusia intermixta (Lepidoptera: Noctuidae), are commonly found together in lettuce, Lactuca sativa L., fields in Japan. Given the marked morphological similarities between these species and the difficulty associated with discriminating between them using only visual cues, we used multiplex polymerase chain reaction (PCR) assay to distinguish between the three target species. Multiplex PCR uses four primers to simultaneously amplif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 24 publications
(22 reference statements)
0
1
0
Order By: Relevance
“…Although mating disruption has been widely used in lettuce Þelds in Japan, infestation by A. nigrisigna larvae has been observed by agricultural researchers and growers. Indeed, we detected a high number of A. nigrisigna larvae in pheromone-treated lettuce Þelds (Hashiyama et al 2011(Hashiyama et al , 2012. This Þnding indicated that the Confuser V system does not work well against A. nigrisigna.…”
mentioning
confidence: 93%
“…Although mating disruption has been widely used in lettuce Þelds in Japan, infestation by A. nigrisigna larvae has been observed by agricultural researchers and growers. Indeed, we detected a high number of A. nigrisigna larvae in pheromone-treated lettuce Þelds (Hashiyama et al 2011(Hashiyama et al , 2012. This Þnding indicated that the Confuser V system does not work well against A. nigrisigna.…”
mentioning
confidence: 93%